Pursuit of national interests through neutralism - "Bhattacharya, Sauripada" (Calcutta, 1978)
This book is explain about India"'s foreign policy in the Nehru Era. Of these studies documenting India"s diplomacy dominated by the posture of non-alignment-cum- neutralism.
Keywords: Neutrality